Epidemiology and morbidity of Epstein-Barr virus infection in pediatric renal transplant recipients: a multicenter, prospective study - Höcker, Britta; Fickenscher, Helmut; Delecluse, Henri-Jacques; Böhm, Stephan; Küsters, Uta; Schnitzler, Paul; Pohl, Martin; John, Ulrike; Kemper, Markus J.; Fehrenbach, Henry; Wigger, Marianne; Holder, Martin; et al. (Clinical infectious diseases, 2013)
Background: The epidemiology and morbidity of Epstein-Barr virus (EBV) infection in pediatric renal transplant recipients have been characterized insufficiently. Methods: In a prospective, multicenter study among 106 pediatric kidney allograft recipients aged 11.4 ± 5.9 years, we investigated the epidemiology of EBV infection and the relationship between EBV load, EBV serology, and EBV-related morbidity (posttransplant lymphoproliferative disease [PTLD] or symptomatic EBV infection, defined as flu-like symptoms or infectious mononucleosis). Results: EBV primary infection occurred in 27 of 43 (63%) seronegative patients and reactivation/reinfection in 28 of 63 (44%) seropositive patients. There was no association between the degree or duration of EBV load and EBV-related morbidity: The vast majority (17 of 18 [94%]) of patients with a high, persistent EBV load remained PTLD-free throughout a follow-up of 5.0 ± 1.3 years, while 2 of 3 (66%) patients with EBV-related PTLD exhibited only a low EBV load beforehand. Eight of 18 (44%) patients with a high, persistent EBV load remained asymptomatic during a follow-up of 5.3 ± 2.9 years. Multivariate analysis identified the EBV high-risk (D+/R–) serostatus (odds ratio [OR], 7.07; P < .05), the presence of human leukocyte antigen (HLA)–DR7 (OR, 5.65; P < .05), and the intensity of the immunosuppressive therapy (OR, 1.53; P < .01) as independent risk factors for the development of a symptomatic EBV infection. Conclusions: Presence of EBV high-risk seroconstellation, HLA-DR7, and intensity of immunosuppressive therapy are significant risk factors for a symptomatic EBV infection, whereas there is no close association between the degree or duration of EBV load and EBV-related morbidity.
Published: 05 October 2012
Gesehen am 12.07.2018